Genre, ethnicité et participation politique : le cas des femmes kurdes en Iran - Fatemeh Karimi (Genre, Sexualité et Société)
This article analyzes the intertwining of ethnicity and gender in the political participation of Kurdish women in Iran before, during and after the 1979 revolution until the late 1980s when the Kurdish political forces recognized their defeats at the both political and armed, and suffer from the exile of most of their members – especially in Europe. Organized in two parts, this article analyzes the reasons for the participation of Kurdish women in the political life of this period, their claim and the modality of their participation. For the analysis of these elements, this article looks at the experiences of former activists and fighters of Komala, a far-left Kurdish political organization. The political involvement of these women is very little documented, so much of the information presented in this article will come from testimonies collected between the years 2014-2018 as part of a sociological research.